Pengaruh PDRB, Pajak, dan Retribusi Sektor Industri terhadap Tingkat Pengangguran dan Indeks Pembangunan Manusia di Kabupaten Mimika - Pritty Laluhun; Nur Khalimatus Sadia; Rulan L. Manduapessy (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to analyze the effect of industrial sector development on economic development in Mimika Regency. Economic development in this study is reflected through two main indicators, namely the unemployment rate and the Human Development Index (HDI). The research employs a quantitative associative approach using secondary time-series data obtained from the Central Bureau of Statistics for the period 2014–2023. The analytical method applied is the Autoregressive Distributed Lag (ARDL) model, which allows the examination of both short-run and long-run relationships among variables. The results indicate that the Gross Regional Domestic Product (GRDP) of the industrial sector in the current period has a significant effect on the unemployment rate, while industrial sector taxes show no significant effect. Industrial sector retribution in the current period is found to significantly affect unemployment. However, the findings reveal that industrial sector GRDP, taxes, and retribution do not have a significant impact on the HDI, either in the current or previous periods. These results suggest that while industrial development contributes to employment absorption, its role in improving human development outcomes in Mimika Regency remains limited